2022
DOI: 10.1097/cm9.0000000000001869
|View full text |Cite
|
Sign up to set email alerts
|

Resuscitation fluids as drugs: targeting the endothelial glycocalyx

Abstract: Fluid resuscitation is an essential intervention in critically ill patients, and its ultimate goal is to restore tissue perfusion. Critical illnesses are often accompanied by glycocalyx degradation caused by inflammatory reactions, hypoperfusion, shock, and so forth, leading to disturbed microcirculatory perfusion and organ dysfunction. Therefore, maintaining or even restoring the glycocalyx integrity may be of high priority in the therapeutic strategy. Like drugs, however, different resuscitation fluids may h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 69 publications
(169 reference statements)
0
6
0
Order By: Relevance
“…The systemic inflammatory response and excessive release of catecholamines caused by sepsis can lead to excessive degradation of the vascular endothelial glycocalyx, causing damage to vascular endothelial cells [62,63]. Destruction of pulmonary capillary endothelial cells leads to increased pulmonary capillary permeability, which in turn leads to pulmonary interstitial edema and gravity-dependent consolidation [46].…”
Section: Sepsismentioning
confidence: 99%
“…The systemic inflammatory response and excessive release of catecholamines caused by sepsis can lead to excessive degradation of the vascular endothelial glycocalyx, causing damage to vascular endothelial cells [62,63]. Destruction of pulmonary capillary endothelial cells leads to increased pulmonary capillary permeability, which in turn leads to pulmonary interstitial edema and gravity-dependent consolidation [46].…”
Section: Sepsismentioning
confidence: 99%
“…Fluid resuscitation is one of the most commonly used interventions in hemodynamic therapy [61]. Based on the understanding of the critical unit, the strategy of fluid resuscitation has gradually moved from targeting macrocirculation to targeting endothelial cells, which is reflected by the increasing attention of clinicians to the effects of different types of resuscitation fluids, which may aggravate or improve glycocalyx shedding, endothelial activation, and coagulation dysfunction [62]. Many experiments have demonstrated that crystalloids and gelatins may cause the degradation and shedding of the EGC; on the contrary, plasma and albumin have protective effects on vascular endothelium and microcirculation [63][64][65].…”
Section: Microcirculation-guided Treatmentsmentioning
confidence: 99%
“…The increasing emphasis on microcirculation and the endothelium has greatly impacted the choice of resuscitation fluid in clinical practice. One proposal is to increase the priority of hyperoncotic albumin solutions [62]. Although there have been no high-quality clinical studies to confirm the effects of albumin and plasma on the prognosis of critically ill patients, their potential benefits may inspire new ideas for clinical decision-making.…”
Section: Microcirculation-guided Treatmentsmentioning
confidence: 99%
“…Further tests on drugs like Sulodexide, a combination of heparin-sulfate like compound shown to regenerate the glycocalyx in a mouse model of sepsis, that also restores glycocalyx volume in diabetics, should be studied further in critical care [ 169 ]. FFP has shown benefit in animal models as well as models of haemorrhagic shock but there are no high quality studies of its effects restoring the glycocalyx in critical illness [ 170 , 171 ].…”
Section: Future Directionsmentioning
confidence: 99%